Synaptic expression of TAR-DNA-binding protein 43 in the mouse spinal cord determined using super-resolution microscopy - Broadhead, Matthew J.; Ayvazian-Hancock, Ani; Doucet, Katherine; Kantelberg, Owen; Motherwell, Lesley; Zhu, Fei; Grant, Seth G. N.; Horrocks, Mathew H.; Miles, Gareth B. (Frontiers in Molecular Neuroscience, 2023)
Amyotrophic Lateral Sclerosis (ALS) is characterised by a loss of motor neurons in the brain and spinal cord that is preceded by early-stage changes in synapses that may be associated with TAR-DNA-Binding Protein 43 (TDP-43) pathology. Cellular inclusions of hyperphosphorylated TDP-43 (pTDP-43) are a key hallmark of neurodegenerative diseases such ALS. However, there has been little characterisation of the synaptic expression of TDP-43 inside subpopulations of spinal cord synapses. This study utilises a range of high-resolution and super-resolution microscopy techniques with immunolabelling, as well as an aptamer-based TDP-43 labelling strategy visualised with single-molecule localisation microscopy, to characterise and quantify the presence of pTDP-43 in populations of excitatory synapses near where motor neurons reside in the lateral ventral horn of the mouse lumbar spinal cord. We observe that TDP-43 is expressed in approximately half of spinal cord synapses as nanoscale clusters. Synaptic TDP-43 clusters are found most abundantly at synapses associated with VGLUT1-positive presynaptic terminals, compared to VGLUT2-associated synapses. Our nanoscopy techniques showed no difference in the subsynaptic expression of pTDP-43 in the ALS mouse model, SOD1G93a, compared to healthy controls, despite prominent structural deficits in VGLUT1-associated synapses in SOD1G93a mice. This research characterises the basic synaptic expression of TDP-43 with nanoscale precision and provides a framework with which to investigate the potential relationship between TDP-43 pathology and synaptic pathology in neurodegenerative diseases.